Hot Protestants : a history of Puritanism in England and America - Winship, Michael P. (Michael Paul) (Yale University Press, 2018)
Begun in the mid-sixteenth century by Protestant nonconformists keen to reform England's church and society while saving their own souls, the puritan movement was a major catalyst in the great cultural changes that transformed the early modern world. Providing a uniquely broad transatlantic perspective, this groundbreaking volume traces puritanism's tumultuous history from its initial attempts to reshape the Church of England to its establishment of godly republics in both England and America and its demise at the end of the seventeenth century. Shedding new light on puritans whose impact was far-reaching as well as on those who left only limited traces behind them, Michael Winship delineates puritanism's triumphs and tribulations and shows how the puritan project of creating reformed churches working closely with intolerant godly governments evolved and broke down over time in response to changing geographical, political, and religious exigencies.